ILC‐poiesis: Ensuring tissue ILC differentiation at the right place and time. Issue 1 (2nd November 2018) - Lim, Ai Ing; Di Santo, James P.
Abstract: Innate lymphoid cells (ILCs) represent a family of innate effector cells including NK cells, lymphoid tissue inducer (LTi) cells, and distinct ILC1, ILC2, and ILC3 subsets that produce IFN‐γ, IL‐5/IL‐13, and IL‐17A/IL‐22, respectively. ILCs accumulate at mucosal sites and can promote the first‐line defense against infection. ILCs are also implicated in tissue repair and can either pre‐empt, or alternatively, exacerbate inflammation. Studies in mice have identified ILC precursors in fetal liver and adult BM that have diverse lineage potential. As such, these sites have been considered as the 'factories' to generate mature ILC. Here, we summarize knowledge concerning murine and human ILC development and discuss the recent identification of circulating multipotent and unipotent ILC precursors. We propose an alternative model of "ILC‐poiesis", whereby blood ILC precursors migrate into tissues to complete their differentiation into mature ILC subsets under the influence of local environmental factors. Within this framework, ILC‐poiesis guarantees appropriate ILC generation at the right place and the right time. We further discusss the potential applications of circulating ILC precursors for cell therapy of human disease. Abstract : "ILC‐poiesis" describes the process whereby circulating ILC precursors are activated in tissues by local inflammatory signals that trigger their proliferation and differentiation into mature ILCs.